Microbial Cell-Free DNA Identifies the Causative Pathogen in Infective Endocarditis and Remains Detectable Longer Than Conventional Blood Culture in Patients with Prior Antibiotic Therapy. (10th June 2022) - Eichenberger, Emily M; Degner, Nicholas; Scott, Erick R; Ruffin, Felicia; Franzone, John; Sharma-Kuinkel, Batu; Shah, Pratik; Hong, David; Dalai, Sudeb C; Blair, Lily; Hollemon, Desiree; Chang, Eliza; et al.
Abstract: Background: The diagnosis of infective endocarditis (IE) can be difficult, particularly if blood cultures fail to yield a pathogen. This study evaluates the potential utility of microbial cell-free DNA (mcfDNA) as a tool to identify the microbial etiology of IE. Methods: Blood samples from patients with suspected IE were serially collected. mcfDNA was extracted from plasma and underwent next-generation sequencing. Reads were aligned against a library containing DNA sequences belonging to >1400 different pathogens. mcfDNA from organisms present above a statistical threshold were reported and quantified in molecules per milliliter (MPM). Additional mcfDNA was collected on each subject every 2–3 days for a total of 7 collections or until discharge. Results: Of 30 enrolled patients with suspected IE, 23 had definite IE, 2 had possible IE, and IE was rejected in 5 patients by modified Duke Criteria. Only the 23 patients with definite IE were included for analysis. Both mcfDNA and blood cultures achieved a sensitivity of 87%. The median duration of positivity from antibiotic treatment initiation was estimated to be approximately 38.1 days for mcfDNA versus 3.7 days for blood culture (proportional odds, 2.952; P = .02771), using a semiparametric survival analysis. mcfDNA (log10) levels significantly declined (−0.3 MPM log10 units, 95% credible interval −0.45 to −0.14) after surgical source control was performed (pre- vs postprocedure, posterior probability >0.99). Conclusion: mcfDNA accurately identifies the microbial etiology of IE. Sequential mcfDNA levels may ultimately help to individualize therapy by estimating a patient's burden of infection and response to treatment. Abstract : Microbial cell-free DNA accurately identified the microbial etiology of infective endocarditis, was detectable for significantly longer than conventional blood cultures, and rapidly declined with surgical source control.